The Effects of Adversity Quotient And Spiritual Quotient on Teacher Performance - muztaba, muztaba; Bahri, Syamsul; Farizal, Farizal (Asian Journal of Science Education, 2020)
This study aims to examine and find out empirical data about the effect of adversity quotient and spiritual quotient on the performance of Al-Azhar Elementary School teachers, Depok City separately or simultaneously. In this study, the authors used a survey method with a correlational approach to quantitative data obtained from the research object. The type of analysis used is correlation and regression analysis which is described descriptively. The results of this study are: First, there is a positive and significant influence between adversity quotient and spiritual quotient of teachers in SD Al-Azhar 46 Depok City. Secondly, there is a positive and significant influence between spiritual quotient and teacher performance of Sd Al-Azhar 46 Depok City. There is a significant positive between Adversity Quotient and Spiritual Quotient. Fourth, there is a positive and significant influence between adversity quotient and spiritual quotient together (simultaneously) with the performance of teachers at SD Al-Azhar 46 Depok City.Keywords: Adversity quotient, spiritual quotient, teacher performance